2013
DOI: 10.3762/bjoc.9.73
|View full text |Cite
|
Sign up to set email alerts
|

1-n-Butyl-3-methylimidazolium-2-carboxylate: a versatile precatalyst for the ring-opening polymerization of ε-caprolactone and rac-lactide under solvent-free conditions

Abstract: SummaryThe ring-opening polymerization of ε-caprolactone (ε-CL) and rac-lactide (rac-LA) under solvent-free conditions and using 1-n-butyl-3-methylimidazolium-2-carboxylate (BMIM-2-CO2) as precatalyst is described. Linear and star-branched polyesters were synthesized by successive use of benzyl alcohol, ethylene glycol, glycerol and pentaerythritol as initiator alcohols, and the products were fully characterized by 1H and 13C{1H} NMR spectroscopy, gel permeation chromatography (GPC), and differential scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Not surprisingly some of these techniques have also recently been applied in the ROP of cyclic esters. The groups of Taton, Plasseraud and Buchmeiser reported on the polymerization of ϵ ‐CL by NHCs thermally generated from CO 2 adducts (Fig. ), while Brulé et al presented a ‘benchtop’ setup for the preparation of poly( β ‐butyrolactone) using the same type of adducts.…”
Section: Ring‐opening Polymerizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly some of these techniques have also recently been applied in the ROP of cyclic esters. The groups of Taton, Plasseraud and Buchmeiser reported on the polymerization of ϵ ‐CL by NHCs thermally generated from CO 2 adducts (Fig. ), while Brulé et al presented a ‘benchtop’ setup for the preparation of poly( β ‐butyrolactone) using the same type of adducts.…”
Section: Ring‐opening Polymerizationsmentioning
confidence: 99%
“…Some NHC–CO 2 adducts that have been used for in situ liberation of free NHCs for lactone polymerization …”
Section: Ring‐opening Polymerizationsmentioning
confidence: 99%
“…Such NHCs promote the transesterification between alcohols and organic esters 50 and have been investigated for ring opening polymerisation, in which the NHC is generated and has been shown to proceed via nucleophilic attack. 51 For the cyclocarbonation reaction, reactions with 13 C 3 -labelled DMC and 1 in a 1.5 : 1 molar ratio run in DMSO-d 6 provided more insight into the mechanism of reaction. 1 H, 13 C and HMBC 2D NMR experiments allowed the identification of a 13 C-labelled methyl ester group attached to the imidazolium compound and a signal attributed to 13 Clabelled methanol ( Fig.…”
Section: Homogeneous Nhcsmentioning
confidence: 99%
“…Waymouth et al showed that NHCs are active for the ROP of TMC and other groups showed the effective use of carbene‐carboxylates for lactid, and β‐butyrolacton polymerization. A strong dependence on the structure of the carbene catalyst for the polymerization of esters was found.…”
Section: Introductionmentioning
confidence: 99%